Let the Problems Come, and Let the Learning Take Place - Martha E. Duque; Melina Escobar (Asociación Colombiana de Profesores de Ingles, 2016)
In a sense, every language class can be said is a multilevel or mixed ability class. This is because every class is made up of a group of individuals, and each of these individuals in some extent, has a different control, knowledge and ability of the language, which means that among them there is a marked difference in language level.